Response to 'Cutaneous squamous cell carcinoma is associated with Lynch syndrome: widening the spectrum of Lynch syndrome‐associated tumours'. (24th March 2022) - Sowter, Peter; Santibanez‐Koref, Mauro; Jackson, Michael S.; Borthwick, Gillian M.; Burn, John; Rajan, Neil; Gallon, Richard
Abstract :